Supemumerary Kidney (triple kidney) with horseshoe component: a case report (2013)
Supermumerary kidney is a rare congenital anomaly of the urinary system with less tha 100 cases documented in literature worldwide.Very rarely documented is the fused supermumerary kidney and horseshoe components with unknown incidence, due to the rarity of this complex anomaly. We hereby present a rare case of complex renal anomalies of fused supernumerary kidneys with horseshoe component misdiagnosed as an abdominal tumor on ultrasound, incidentally discovered at Computed Tomography.